1997
DOI: 10.1073/pnas.94.1.91
|View full text |Cite
|
Sign up to set email alerts
|

The motor domain and the regulatory domain of myosin solely dictate enzymatic activity and phosphorylation-dependent regulation, respectively

Abstract: While the structures of skeletal and smooth muscle myosins are homologous, they differ functionally from each other in several respects, i.e., motor activities and regulation. To investigate the molecular basis for these differences, we have produced a skeletal͞smooth chimeric myosin molecule and analyzed the motor activities and regulation of this myosin. The produced chimeric myosin is composed of the globular motor domain of skeletal muscle myosin (Met 1 -Gly 773 ) and the C-terminal long ␣-helix domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…A chimeric HMM consisting of a skeletal motor domain and the neck and rod from smooth muscle myosin was recently shown to decrease its actin-activated ATPase activity from 4.3 to 0.5 s Ϫ1 upon dephosphorylation (5). This result suggested that the presence of the smooth muscle LC-binding region conferred the motor domain with the ability to inhibit phosphate release.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…A chimeric HMM consisting of a skeletal motor domain and the neck and rod from smooth muscle myosin was recently shown to decrease its actin-activated ATPase activity from 4.3 to 0.5 s Ϫ1 upon dephosphorylation (5). This result suggested that the presence of the smooth muscle LC-binding region conferred the motor domain with the ability to inhibit phosphate release.…”
mentioning
confidence: 65%
“…A more stringent test of whether the regulatory domain is the sole determinant of regulation is to analyze the properties of a chimera with the smooth muscle neck and rod attached to a heterologous motor domain. Using this strategy, it was reported that a chimera containing the motor domain from skeletal muscle myosin and the neck and rod from smooth muscle HMM conferred a 9-fold degree of regulation upon this previously unregulated motor (5). Here, the properties of a similar construct containing the motor domain from an unconventional myosin V and the neck and rod from smooth muscle HMM were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The global rise in intracellular Ca 2ϩ initiates actin-myosin interaction by activating myosin light chain kinase (MLCK). 23,24 To clarify the link between PI3K and Ca 2ϩ handling, Northcott et al 2 demonstrate that LY294002, like an L-type Ca 2ϩ blocker, abolished Ca 2ϩ -induced spontaneous tone in aorta of hypertensive rats, whereas LY294002 had no effect on the enhanced contraction induced by BayK8644, a direct L-type channel agonist. LY294002 also corrected KCl or norepi-nephrine-induced contraction in hypertensive rats.…”
Section: Roles Of Pi3k Signaling In Smooth Muscle Cellsmentioning
confidence: 99%
“…In contrast to the RLC, the ELC appears to be less important to regulation because it can be replaced by the skeletal isoform or removed entirely with little effect on regulation (17). The requirements for full regulation in smooth muscle myosin are complex, because of a subtle interplay between the light chain domain, the actin binding loop (18), the catalytic domain (19), and the heavy chain sequence within the light chain domain (20).…”
mentioning
confidence: 99%